Measuring library anxiety of international students of U.P. Diliman - Mateo, Marc Paul R. (2016)
According to studies, international students go to the Philippines primariy to study English writing and speaking skills, meet new friends, experience a nes culture, etc. They face many difficulties studying abroad. Aside from cultural adjustments, they also adjust to the new education system, new people, new places, new weather, etc. The library is one of the areas that international students need to adjust. It was discovered that students experience the feeling of being lost and inadequacy during their initial visits to the library. Library anxiety is the term used to describe these feelings experienced by students.